The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1037/bne0000326
|View full text |Cite
|
Sign up to set email alerts
|

Timing is everything: Developmental differences in the effect of chronic corticosterone exposure on extinction retention.

Abstract: Adolescence is noted as a time of “storm and stress.” In this developmental stage both rodents and humans exhibit an impairment in the extinction of learned fear; however, this impairment can be alleviated, at least in rodents, by increasing the amount of extinction training given or by administering the partial NMDA receptor agonist D-Cycloserine. In the present study we explored whether the benefits of these treatments would be reduced by chronic exogenous corticosterone (a commonly studied stress-related ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…In terms of effects on fear extinction in adolescence, chronic stressor exposure by restraint or social instability in adolescence impairs the acquisition or retention of extinction memories when tested in adolescence relative to non-stressed controls [100,101,102]. Adolescence appears to be a particularly stress-sensitive developmental period in terms of fear regulation because animals are more susceptible to extinction deficits when stress occurs during adolescence compared to when it occurs in the juvenile period [103] or adulthood [102,104]. Further, such deficits induced by adolescent stress are long-lasting, persisting into adulthood [104].…”
Section: Disruption By Chronic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of effects on fear extinction in adolescence, chronic stressor exposure by restraint or social instability in adolescence impairs the acquisition or retention of extinction memories when tested in adolescence relative to non-stressed controls [100,101,102]. Adolescence appears to be a particularly stress-sensitive developmental period in terms of fear regulation because animals are more susceptible to extinction deficits when stress occurs during adolescence compared to when it occurs in the juvenile period [103] or adulthood [102,104]. Further, such deficits induced by adolescent stress are long-lasting, persisting into adulthood [104].…”
Section: Disruption By Chronic Stressmentioning
confidence: 99%
“…The consequences of adolescent stress on fear extinction are important clinically when considering strategies for chronically stressed youth presenting for treatment of anxiety disorders. This is because chronic exposure to the stress hormone corticosterone in adolescence reduces the benefit of two approaches that augment extinction retention in adolescent rats, namely extra extinction training [103,104] and pharmacological augmentation by DCS [103]. Such results suggest that a history of chronic stress could further reduce the efficacy of anxiety treatments in adolescents.…”
Section: Disruption By Chronic Stressmentioning
confidence: 99%
“…Adolescent rats exposed to corticosterone displayed significantly higher CS-elicited freezing at the extinction retention test, as compared to rats exposed to vehicle or water, which did not differ from each other, following extended extinction training ( Den et al, 2014 ). In another set of experiments, Stylianakis et al (2019) replicated those effects and further reported that pharmacological enhancement of extinction retention by DCS in adolescent rats was abolished when animals had been exposed to chronic corticosterone in their drinking water. These findings suggest that two methods that have been shown to ameliorate the extinction retention deficit in non-stressed adolescent rats, extended extinction training and DCS, do not facilitate extinction retention in adolescents exposed to chronic stress.…”
Section: Introductionmentioning
confidence: 70%
“…Placebo pellets, purchased from the same supplier, were the same size and consisted of the same matrix without the corticosterone. Dose and duration of hormone administration were chosen based on the average daily dose consumed by rats across 7 days of corticosterone administration in drinking water in our previous studies on extinction in stressed adolescent rats (i.e., Den et al, 2014 ; Stylianakis et al, 2019 ). Before implantation of pellets, animals received a pre-emptive subcutaneous (s.c.) injection of the non-steroidal anti-inflammatory analgesic Carprofen (5 mg/kg; 1 ml/kg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation